2021
DOI: 10.3389/fmed.2021.727412
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Microscopic Colitis Have Altered Levels of Inhibitory and Stimulatory Biomarkers in Colon Biopsies and Sera Compared to Non-inflamed Controls

Abstract: Introduction: Microscopic colitis (MC) is an inflammatory bowel condition with two subtypes, lymphocytic colitis (LC) and collagenous colitis (CC). Unlike patients with ulcerative colitis (UC) and non-inflamed individuals, MC patients have reduced risk of developing colorectal cancer, possibly due to increased immune surveillance in MC patients.Aim: To examine differences in levels of immunomodulatory molecules, including those involved in immune checkpoint mechanisms, in sera from patients with MC and in colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…For example, an observational study focusing on gastrointestinal immune-related adverse events of ICIs has suggested that patients treated with anti-CTLA4 antibodies show a higher incidence of events and more severe symptoms ( Yamada et al, 2021 ). Furthermore, compared with non-inflamed individuals, CTLA4 is increased in biopsies from UC ( Lushnikova et al, 2021 ). In fact, as shown by the results of immune infiltration analysis, the expression level of CTLA4 is strongly associated with many types of immune cells in UC.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an observational study focusing on gastrointestinal immune-related adverse events of ICIs has suggested that patients treated with anti-CTLA4 antibodies show a higher incidence of events and more severe symptoms ( Yamada et al, 2021 ). Furthermore, compared with non-inflamed individuals, CTLA4 is increased in biopsies from UC ( Lushnikova et al, 2021 ). In fact, as shown by the results of immune infiltration analysis, the expression level of CTLA4 is strongly associated with many types of immune cells in UC.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only a limited number of studies have investigated soluble PD-1/PD-L1 in CRC. Compared to control subjects, both protein levels were significantly lower in CRC patients, but with a large SD [ 47 ], and significant alterations can be found in various colitis forms as well [ 48 ]. Higher circulating PD-L1 levels have been found to be associated with a higher degree of tumor differentiation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%